2021
DOI: 10.3390/cancers13215294
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Size >5 cm and Harvested LNs <12 Are the Risk Factors for Recurrence in Stage I Colon and Rectal Cancer after Radical Resection

Abstract: Recurrence can still occur even after radical resection of stage I colorectal cancer (CRC). This study aimed to identify subgroups with a high risk for recurrence in the stage I CRC. We retrospectively reviewed prospectively collected data of 1952 patients with stage I CRC after radical resection between 2002 and 2017 at our institute. 1398 (colon, 903 (64.6%), rectum, 495 (35.4%)) were eligible for analysis. We analyzed the risk factors for recurrence and survival. During the follow-up period (median: 59 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Multivariate analysis showed higher lymph node metastasis rates were more likely to be discovered in increasing tumor size (Ramai et al 2021 ). According to the previous articles, the larger the tumor size, the worse the prognosis of the patients with colorectal SRCC (Jung et al 2021 ; Burzykowski et al 2019 ).…”
Section: Discussionmentioning
confidence: 96%
“…Multivariate analysis showed higher lymph node metastasis rates were more likely to be discovered in increasing tumor size (Ramai et al 2021 ). According to the previous articles, the larger the tumor size, the worse the prognosis of the patients with colorectal SRCC (Jung et al 2021 ; Burzykowski et al 2019 ).…”
Section: Discussionmentioning
confidence: 96%
“…In our study, the OS and DFS were lower in the rsCRC group, with higher mortality and recurrence hazards. Some studies reported the presence of the CRC tumor on the left side to be an independent bad prognostic factor for the disease outcome [ 26 ]. Moreover, a possible explanation for the lower survival in the rsCRC group in our study was the higher frequency of MMR-proficient (i.e., microsatellite stable (MSS)) status in the rsCRC.…”
Section: Discussionmentioning
confidence: 99%
“…In the Cox proportional hazards model, the regression coe cients of these prognostic factors indicated the contribution of each factor to OS. Based on clinical guidelines [1,15], published studies [22][23][24][25] and multivariate analysis, all the selected potential prognostic variables were converted to a risk score of each prognostic factor after being multiplied by 5 and rounded.…”
Section: Discussionmentioning
confidence: 99%